Clarissa Tossin - to take root among the stars - Erger, Georgia (Frye Art Museum, 2023)
"Clarissa Tossin (born 1973, Porto Alegre, Brazil) works across artistic mediums including film, sculpture, and drawing to explore the intersections of climate change and global capitalism's frontier mythologies. Published by the Frye Art Museum as the artist's first monograph, this catalogue presents an overview of Tossin's career through full-color reproductions that span from 2008 to 2023, including images of several new artworks commissioned by the Frye. Through their seamless melding of synthetic and organic materials, the artist's works embody the tension between capitalist-driven ecological destruction and reciprocal caretaking approaches of Indigenous communities. Essays by curator Vic Brooks, writer Leslie Dick, and exhibition curator Georgia Erger offer intimate assessments of the artist's practice at a timely moment
Includes bibliographical references
Keywords: Tossin, Clarissa -- 1973-; Tossin, Clarissa / 1973- / Exhibitions; Human ecology in art / Exhibitions; Ausstellungskatalog -- Frye Art Museum -- 07.10.2023-07.01.2024 -- Seattle, WA